AC Conductivity and Dielectric Properties of Strontium-Lead Borate Glasses - Hisam, R.; K. Yahya, A.; Said, Dayana; F. Mustafa, M. (International Journal of Engineering and Technology, 2018)
The AC conductivity and dielectric properties of strontium-lead borate glasses with composition of (90-x)B2O3-10PbO-xSrO (x = 20, 25, 30, 35, 40, 45) were studied in the frequency range of 0.01 Hz to 106 Hz at room temperature to investigate the effects of SrO in the glasses. The variation of AC conductivity with SrO content showed a minimum value at x = 25 mol% before increasing to 25 < x ≤ 35 mol%, followed by a slight decrease of x > 35 mol%. Meanwhile, dielectric constant showed a minimum at x = 25 mol% before increasing to x > 25 mol%. The decrease at x = 25 mol% coincided with the σAC drop at the same concentration. This decrease could be associated with the increasing number of bridging oxygens, which restricted dipole movement. The electric modulus of the investigated samples showed that the trend of the imaginary part of the electrical modulus (M″) was in tandem with the behaviour of AC conductivity.